Tingkat Selektifitas Kelompok Perempuan Koperasi 64 Bahari Dalam Menggunakan Media Sosial Di Era Teknologi Informasi Dan Komunikasi - maria yuliastuti; Akhsaniyah (Jurnal Sosial-Politika, 2021)
Starting from the understanding conveyed by Severin and Tankard (2005: 93), the audience is considered active in selecting the media they use. In this case, the Women's Cooperative 64 Bahari Group has tried to choose the mass media according to their needs as a medium for doing business. Through the internet, they personally sell seafood, either fresh or processed fish, although they are still experiencing some difficulties. Selling online activities using either Facebook (FB) or Instagram (IG) is easier and cheaper. However, not every person from the 64 Bahari Women's Cooperative Group has an Android, and even if it does, it doesn't mean that they can operate it properly, especially to use FB or IG. The result is that even though it is already in the selective retention stage, the results of the selective level are still low. Many factors cause this, some of which are the ability of the 64 Bahari Women's Cooperative Group in the use of Information and Communication Technology. This condition ultimately affects the selectivity of the media, especially the 64 Bahari Women's Cooperative Group in using Facebook and Instagram as a medium for doing business.